(untitled) (American Journal of Innovation in Science and Engineering, 2025)
The treatment of fatty acid industrial wastewater is a significant challenge due to the high content of organic and inorganic materials that can pollute the environment. One of the effective methods to overcome this problem is electrocoagulation. The purpose of this study was to analyze the effect of contact time and distance between electrodes in reducing the parameters of fatty acid industrial wastewater. In this study, the electrodes used were Aluminum (Al) as the Anode and Iron (Fe) as the Cathode. The electrocoagulation process was carried out using a voltage of 5 volts with a time variation of 75 minutes, 90 minutes, and 105 minutes and a distance between electrodes of 1 cm, 2 cm, and 3 cm. From this study, it was found that the contact time at 105 minutes and the distance between electrodes at 3 cm could raise the pH to 7.3, reduce the COD concentration to 70 mg/L, and reduce the TSS concentration to 2 mg/L contained in the fatty acid industrial wastewater. However, TSS levels often change due to particles that have not completely settled, which can result in sludge contamination when taking TSS test samples.